International Cooperation and Knowledge Transfer Processes - López López, Wilson; Pontificia Universidad Javeriana (2013)
We have recently launched a new initiative for international cooperation in Psychology, led by Agnaldo Garcia from Brazil, researchers from Chile, Argentina, Peru and Colombia, and myself as a coordinator. The tool stemming from it is http:// psicologiacoopera.org/, a virtual space that we hope helps increase cooperation in our region. Our mission is as follows: “The International Scientific Psychology Network (ISPN) aims at promoting the advancement of Psychology in Spanish and Portuguese-speaking countries through international scientific cooperation: (1) among Spanish and Portuguese-speaking Psychology researchers; (2) connecting Spanish- and Portuguese-speaking Psychology researchers with scholars from all over the world regardless of language and nationality.” We have a set of concrete initial actions: “(1) Identification of Researchers and Themes Investigated - ISPN invites all Spanish- and Portuguese-speaking Psychology researchers to become a member, submitting some basic information related to her/his scientific activities. (2) Diffusion of Research Production and Interests - The website will publicize the scientific production and research interests of all ISPN members to promote the visibility of Spanish- and Portuguese-speaking Scientific Psychology (3) Annual Reviews of Scientific Psychology in Spanish/Portuguese - ISPN will publish annual reviews covering different areas of Psychology investigation in Spanish- and Portuguese-speaking countries (in English) to promote its visibility. (4) Submit a Proposal - Authors interested in preparing critical reviews of specific Psychology areas are invited to submit a proposal (in English, Spanish, or Portuguese). The Annual Reviews aim at making research in Psychology produced in Spanish and Portuguese available to an international wider audience, promoting its visibility and citation.” In just a few days after its launch, our tool reached over 250 researchers from 21 countries and workgroups have already been created. Surely the platform will continue its consolidation and will enable the maximisation of cooperation processes. We hope that groups use this tool to share documents, discuss and create synergies that lead them to collaborate and transfer knowledge. We will also be linking Open Source systems in the portal, such as Redalyc, SciELO, Pepsic, the Psychology Virtual Library and free citation statistics websites such as Google Scholar, Scimago Journal and Country Rank, and also commercial systems such as WoS JCR. Researchers use these and other systems to find knowledge usage information, which they can use in turn to increase cooperation. It is clear that one of the biggest challenges of our regional Psychology is that the visibility of Open Access is reflected in its use. We also understand that we need to develop new ways of measuring this use and of getting cooperation to become a critical source of this process. We hope that tools such as the one we just presented fit into this perspective.